A new tool for assessment of mould growth on building materials - Aibinu, Abiodun Musa; Salami, Momoh Jimoh Emiyoka; Shafie, Amir Akramin; Bamgbopa, Ibrahim A.; Ali, Maisarah; Jahn Kassim, Puteri Shireen (2009)
Mould growth in indoor environments; has been of concern in the built environments, particularly in the hospital, library and residential environment. The phenomenon of Sick Building Syndrome (SBS) and Building Related Illness (BRI) have also been attributed to mould exposure in the indoor environment. Despite the growing concern over mould infestation on building materials and its presence even in hospital and library environment, little have been reported on the development of an objective mould assessment tool and criteria for measuring the level of severity of such unwanted phenomenon. A new three stage mould growth assessment tool on building materials is proposed in this paper. The acquired images undergo preliminary processing stage for color space conversion, noise filtering, illumination equalization and clustering into two distinct classes. The Mould Infestation Analysis and classification distinguish between candidate mould growth and other anatomical information in the acquired image by the use of image intensity, shape, size and ratio of axes. The Mould Grading stage uses the result of Ratio Test (RT), Compactness Test (CT ) and Visual Test (VT) in calculating the Damaged Index on such building material. Results obtained from application of this technique on acquired digital images indicates the appropriateness of this technique in enhancing the visual assessment and providing a concise and precise grading value for mould infested building materials.